Strategies for engineering a two-celled C(4) photosynthetic pathway into rice - Kajala, Kaisa (Journal of experimental botany, 2011)
Every day almost one billion people suffer from chronic hunger, and the situation is expected to deteriorate with a projected population growth to 9 billion worldwide by 2050. In order to provide adequate nutrition into the future, rice yields in Asia need to increase by 60%, a change that may be achieved by introduction of the C(4) photosynthetic cycle into rice. The international C(4) Rice Consortium was founded in order to test the feasibility of installing the C(4) engine into rice. This review provides an update on two of the many approaches employed by the C(4) Rice Consortium: namely, metabolic C(4) engineering and identification of determinants of leaf anatomy by mutant screens. The aim of the metabolic C(4) engineering approach is to generate a two-celled C(4) shuttle in rice by expressing the classical enzymes of the NADP-ME C(4) cycle in a cell-appropriate manner. The aim is also to restrict RuBisCO and glycine decarboxylase expression to the bundle sheath (BS) cells of rice in a C(4)-like fashion by specifically down-regulating their expression in rice mesophyll (M) cells. In addition to the changes in biochemistry, two-celled C(4) species show a convergence in leaf anatomy that include increased vein density and reduced numbers of M cells between veins. By screening rice activation-tagged lines and loss-of-function sorghum mutants we endeavour to identify genes controlling these key traits